Narrative Study: Soft Skills Based on the Life Experiences of Culinary Entrepreneurs - Rahman, Luthfi Riyadh; Wahyuni, Nur; Wati, Ika Wahyu Kusuma; Indra, Muhammad; Widari, Tika (Juwara: Jurnal Wawasan dan Aksara, 2025)
Entrepreneurship is one of the goals of vocational education besides working and continuing education. Around 85% of soft skills can answer the success of students or vocational graduates including culinary majors. But there are many obstacles that must be faced, such as tight competition in the world of work and even the difficulty of building your own business. With these problems, we aim to deepen some of the soft skills needed by students or vocational graduates in the culinary field. The descriptive narrative method with in-depth interviews with culinary maestros was carried out to obtain these soft skills. The culinary maestros we interviewed are some of those who certainly have a culinary business and are easy for us to reach or meet with the accidental sampling technique we found three culinary maestros that we interviewed. Our findings are 1) communicative & friendly; 2) motive or desire & Decision-making including problem solving; 3) perseverance & tenacity; 4) discipline & honesty; 5) cooperation & adaptability; 6) creative & innovative. These findings will have an impact on culinary students or graduates and even other vocational fields, and of course with proper guidance from educators.